Stability of self-reported psychopathic traits in at-risk adolescents in youth welfare and juvenile justice institutions - H. Hachtel; N. Jenkel; K. Schmeck; M. Graf; J. M. Fegert; M. Schmid; C. Boonmann (BMC, 2022)
Abstract Background The purpose of this study was to evaluate the self-reported stability of psychopathic traits in adolescents in residential care (both child welfare and juvenile justice placed juveniles) and potential influencing factors. Methods We applied the Youth Psychopathic traits Inventory (YPI) in a sample of 162 adolescents (M = 15.0 years, SD = 1.3) over a mean time interval of 11 months (min. 6, max. 21 months, SD = 3.14). Results There was no significant difference in YPI total score nor in the three underlying dimensions Grandiose-Manipulative (GM), Callous-Unemotional (CU), and Impulsive-Irresponsible (II) between t1 and t2. Furthermore, approximately 70% of the adolescents showed no clinically significant reliable change on the YPI total score (as measured with the reliable change index), 15% improved, 15% deteriorated. The strongest predictor for psychopathic traits at t2 were psychopathic traits at t1. Additional predictors for higher levels of general psychopathic traits was male sex, for CU-traits male sex and lower levels of internalizing mental health problems, and for II-traits higher levels of externalizing mental health problems. Generally, the three reliable change groups (increase, no change, decrease) did not seemed to differ on relevant factors. Conclusions Our results add to the findings that psychopathic traits are relatively stable in this at-risk group over approximately a 1-year time interval. Research with a longer follow-up time and more time points is warranted to better interpret these results.